Reducing Wait Times for Children’s Developmental Disorders Consultations Via Simplified Primary Care Assessments: Life Sciences-Psychiatry - Kuranami, Takaaki; Kon, Kimiya; Gemba, Kiminori; Oda, Tetsuaki (International Journal of Life Science and Pharma Research, 2024)
The number of children diagnosed with developmental disorders in Japan is increasing annually, primarily assessed byspecialized physicians in pediatrics, pediatric neurology, and child psychiatry. However, medical institutions for children withdevelopmental disorders often have fully booked schedules, forcing long waiting periods until initial consultations can be obtained. Onereason for this is the shortage of specialized medical institutions and specialists. Prolonged waiting periods may not only delayintervention and support but also exacerbate the child’s symptoms and cause psychological distress to the caregivers. Therefore,reducing the waiting period for initial consultations from the perspective of early detection and early support is an urgent issue.However, there is insufficient research on how to shorten the waiting period. Therefore, we focused on local primary care physicians,who are familiar with shortening the waiting time for initial consultations at specialist medical institutions. This aimed to investigatewhether there was a change in the waiting time for initial consultations at specialist medical institutions when local primary carephysicians used a simplified assessment sheet supervised by pediatric specialists, and referrals were made to specialist medical institutionsafter assessment. The participants consisted of 15 individuals referred from primary care physicians to specialist medical institutions and15 who directly visited medical institutions, totaling 30 participants for evaluation. As a result, the group that made appointments andvisited specialist medical institutions directly showed significantly longer waiting periods than those assessed by primary care physiciansand referred to specialist medical institutions (p < 0.05). Assessment and treatment of developmental disorders in early childhood haveprimarily been conducted at specialized medical institutions. Still, using a simplified assessment sheet by primary care physicians suggestsa potential reduction in the waiting time for initial consultations with specialists.